Computer Technology and Teaching of Accounting by Universities in Ghana - Simpson, S.N.Y.; Welbeck, E.E. (My University, 2013)
The past several years have seen phenomenal efforts across the globe to adopt information and communication technology (ICT) in every aspect of education due to the several benefits it presents. The areas that seem to be attracting much attention are teaching, learning and research. Universities in Africa have not been left out in this development, but compared to other countries, regions and continents, very little seems to have been done in assessing the extent of ICT adoption in the teaching and learning of the various disciplines, including accounting. Adopting the survey strategies, this paper explores the use of ICT in the teaching of accounting in African Universities, using evidence from Ghana. Results show that ICT is used in the teaching of accounting by universities; more in public than private universities. Moreover, more accounting students in private universities are exposed to ICT resources like accounting software than the public universities. In addition, PowerPoint presentations, emails, and the internet in general, are the commonly used ICT resources in the teaching of accounting.